Genetic diversity and specialisation of Eudarluca caricis on some graminaceous Puccinia species. (April 2015) - Kajamuhan, A.; Saslis-Lagoudakis, C.H.; Shaw, M.W.
Abstract: Eudarluca caricis is a common hyperparasite of rusts. A total of 100 cultures were isolated from six Puccinia species or forms growing on 10 species of British grasses at two sites approximately 3 km apart. 82 isolates collected in 2005 were partially sequenced at the ITS locus, and amplified fragment length polymorphism profiles generated for 86 isolates from 2005 and 12 from 2007. Partial ITS sequences of most isolates grouped closely, in a clade with previously reported graminaceous Puccinia isolates and a number of Melampsora isolates. A second clade was very distinct and contained mostly isolates from Puccinia poarum on Poa trivialis . All isolates had distinct AFLP haplotypes. The P. poarum isolates were very distinct from isolates collected from other rusts at the same site. Isolates from P. brachypodii f. sp. arrhenatheri growing on Arrhenatherum elatius in 2005 and 2007 at the same location were distinct (P < 0.001). Isolates from each rust or grass in one year and site were more similar than expected from overall variation between isolates (P < 0.001). Isolates from P. coronata on different grasses clustered together (with isolates from P. brachypodii f. sp. poae-nemoralis ), suggesting partial host rust specialisation in E. caricis .